Systematic Management of Character Education to Enhance Student Discipline Through School-Industry Collaboration - Nurdiana Nurdiana; Maman Suherman (Papanda Publisher, 2026)
The Fourth Industrial Revolution demands vocational graduates possess strong discipline alongside technical competencies, yet 25% experience employment difficulties due to weak work ethic rather than skill deficiencies. This qualitative multiple case study examined character education management at SMKN 1 Pangandaran and SMKS Taruna Bangsa Ciamis through observations, interviews, and document analysis. Data were analyzed using Miles and Huberman's framework with triangulation for validity. Management functions operated systematically: planning established four discipline indicators (punctuality, SOP/safety compliance, task responsibility, professional communication); organizing created cross-functional coordination with clear role delineation; implementation combined school-based habituation through Teaching Factory with authentic industrial practice during internships; evaluation employed the CIPP model using rubrics, logbooks, and industry reports. Punctuality improved from 68% to 89%, and safety compliance increased from 72% to 94% during internships. Barriers including teacher preparation gaps, cultural differences, and short internship duration were addressed through professional development, graduated transitions, and standardized assessment instruments. Findings demonstrate that systematic management frameworks effectively bridge school-industry contexts for discipline formation. The study extends social learning and experiential learning theories into vocational character education, providing actionable practices for educators and policymakers while identifying needs for longitudinal research and exploration of higher-order professional competencies.